Kinematics Analysis of a 2PRPaU-2PSS Parallel Mechanism - Zheng Xin; Du Li; Che Linxian; Li Jie; Huang Xin; Lu Jiahong; Yi Hongyu (Jixie chuandong)
Facing the occasion of grasping and sorting, a novel 3T1R planar symmetric parallel mechanism, named 2PRPaU-2PSS PM, is proposed, and its kinematics is analyzed in detail. The degree of freedom and coupling degree are addressed through the position and orientation characteristic (POC) theory. The mathematical models of displacement and orientation, velocity and acceleration analysis are derived by utilizing the vector method. Meanwhile, the nonlinear equations of forward displacement are transformed into one-dimensional equation, thus using the improved grey wolf optimization algorithm to solve this problem. A numerical example is given to verify the correctness of the kinematical mathematical model, the displacement, velocity, and acceleration curves are obtained with the aid of Matlab, and then Adams is used for simulation verification. Finally, the two results are basically consistent, which indicates that the kinematic mathematical models of the discussed mechanism derived are correct and reliable.